KECENDERUNGAN FOKUS TOPIK PRESENTASI MAHASISWA CALON GURU BIOLOGI MENGGUNAKAN TEKNIK PECHA KUCHA 20X20 - Ni Wayan Ekayanti; Gusti Agung Paramitha Eka Putri (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
Pecha Kucha is a concise oral presentation style where the presenter has 20 seconds to describe the main idea of ​​each PowerPoint slide that displays images without text (Nguyen, 2015). the purpose of this study was to analyze the focus of the topic of Pecha Kucha presentations delivered by IV semester students of Biology Education. The research method is classroom action research conducted in three cycles. The study was conducted with a Pecha Kucha-based discussion learning model. The research subjects were 20 semester Biology education students as many as 20 people. This research was carried out from March to May 2018. The results of the study showed that there was a positive impact on the use of Pecha Kucha techniques for presentation activities. Topics, in the first cycle there was a tendency for the selection of physics, chemistry and biology themes, while for the second and third cycles, the tendency to choose presentation topics experienced a shift towards the biological science family. And the conclusion of this research is that the topic of presentation chosen by students has a shift from cycle I to cycle III, namely from collaborative materials of physics, chemistry and biology to only biological material. Submission of presentations using the Pecha Kucha technique has a positive impact on learning activities.